DOES SHARIA HOTEL MEET ITS CRITERIA STUDY OF SOFYAN HOTEL BETAWI, JAKARTA - Marhanah, Sri; Mardhatilla, Dinda (PEOPLE: International Journal of Social Sciences, 2015)
In line with the economic development of sharia in Indonesia, “Sharia” attribute has been widely used as a promotion in a variety business even in hospitality business. The purpose of this study was to determine the profile of the guests of the hotel based on sharia concept and measure the level of Sharia compliance through the Suitability Analysis. The basic concept of this research is to collect a few of expert opinion about the ideal criteria of a sharia hotel-because there has been no detailed criteria which is officially designated by the government about it-then select and set 29 parameters/indicators as Ideal Criteria of Sharia Hotel. Sofyan Hotel Beltway which has declared as a Sharia Hotel selected as the object of the research to test the suitability of the Sariah compliance. The method of the research is descriptive quantitative method through observation, interviews and questionnaires techniques. The results of this research obtain the level of sharia compliance of so fyan Betawi Hotel is in the category of Quite Appropriate in Facility, Appropriate/Good in Service, and Appropriate/Suitable/Conformable on Corporate Governance (Management). Generally the level of Sariah compliance of Sofyan Beltway Hotel is in the category of Appropriate/Suitable/Conformable.